Strategies for Handling Difficult and Tantrum-Throwing Early Childhood Children - Tatik, T; Slamet, Sri (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: This study aims to identify the factors that cause young children to be difficult to control and prone to tantrums, as well as to identify effective strategies for teachers and parents in dealing with such behavior. In addition, this study also seeks to assess the benefits of implementing these strategies on children's emotional and behavioral development in school and home environments.Methodology: The research method used was descriptive qualitative, with data collection techniques through direct observation, interviews with classroom teachers and parents, and documentation. The research subject was one child in group A at BA Aisyiyah Nurul Huda Bercak, Wonosamodro, who exhibited unruly behavior and frequent tantrums. The subject was selected using purposive sampling based on observations of the child's social and emotional behavior at school and at home.Results: The results of the study show that children with difficult behavior tend to withdraw from group activities, have difficulty concentrating, and often exhibit tantrum-like behavior such as crying, screaming, or throwing objects. The contributing factors include the child's inability to control their emotions, inconsistent parenting, and unmet psychological needs. After a collaborative approach was taken between teachers, parents, and therapists, positive changes were seen in the children's behavior, namely the ability to control emotions, focus on activities, and interact better with peers.Application/Originality/Value: This study provides practical contributions for teachers and parents in dealing with unruly children and tantrums through positive strategies, consistent communication, and cross-role collaboration. The originality of this study lies in the direct application of behavior management strategies in rural early childhood education settings, which shows that simple interventions such as behavioral therapy and empathetic approaches can improve children's emotional control and social interaction.